Epstein-Barr Virus Association with Peptic Ulcer Disease - María G. Cárdenas-Mondragón; Javier Torres; Lourdes Flores-Luna; Ricardo Carreón-Talavera; Margarita Camorlinga-Ponce; Ezequiel M. Fuentes-Pananá (Analytical Cellular Pathology)
Background. Helicobacter pylori (HP) infection and nonsteroidal anti-inflammatory drugs (NSAID) use are considered the main risk to develop peptic ulcer disease (PUD). However, PUD also occurs in the absence of HP infection and/or NSAID use. Recently, we have found evidence that Epstein-Barr virus (EBV) reactivation increases the risk to develop premalignant and malignant gastric lesions. Objective. To study a possible association between EBV and PUD. Methods. Antibodies against an EBV reactivation antigen, HP, and the HP virulence factor CagA were measured in sera from 207 Mexican subjects, controls (healthy individuals, n = 129), and PUD patients (n = 78, 58 duodenal and 20 gastric ulcers). Statistical associations were estimated. Results. Duodenal PUD was significantly associated with high anti-EBV IgG titers (p = 0.022, OR = 2.5), while anti-EBV IgA was positively associated with gastric PUD (p = 0.002, OR = 10.1). Conclusions. Our study suggests that EBV reactivation in gastric and duodenal epithelium increases the risk to develop PUD.